Esophageal surface cells in non-erosive reflux disease: A Scanning Electron Microscopical study (SEM) - Myint, Yi Yi; Tun, Ye; Muhamad Amjad, Nasser; Mat Hassan, Mohd Zailani; Rashid, N.L (Microscopy Society of Malaysia, 2012)
Dilated spaces at intercellular junctions (DIS) in prickle cell layers are considered as early signs of acid-initiated damage to these esophageal epithelium. In order to enter the mucosal intercellular spaces, acid and pepsin have to penetrate the intercellular adhesion sites of the most superficial epithelial cells. The aim of this study is to explore intercellular communications superficial esophageal cells in non- erosive reflux disease (NERD) patients. The study group included eight (NERD) patients and five normal controls individuals. Specimens were routinely processed for SEM observations. The nature of intercellular attachments and intercellular spaces between each individual superficial cells of the esophageal mucosa were viewed under SEM. Our results showed that cellular attachments in the superficial cells differ significantly (p value 0.007) among the normal controls and patients with NERD (Chi-Square test, p <0.05 was considered to be statistically significant). Our findings seems to support the concept of abnormal tissue resistance in the pathogenesis of NERD patients.